LANGKAH CINTA PENUH DERITA ETNIS TIONGHOA DI INDONESIA - Bagus Kesuma Yudha, Anak Agung Ngurah (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2020)
Indonesia is known for its diversity of traditions, culture and ethnicity that is spread across various islands in the archipelago. In forming the character of Indonesian society to be what it is today, it cannot be denied by the role of several ancestors who came from various directions and settled in Indonesia. One of them is the ethnic Chinese (Tionghoa) who helped develop the way of culture to social life which is still adapted until this day. Also with the various dark stories that accompany, the journey of ethnic Chinese (Tionghoa) often becomes a scourge for themselves when faced with the momentum that corners their lives in the name of ethnicity in the archipelago.